Engaging in textbook writing as deliberate practice: How two expert ELT textbook writers use metacognitive strategies while working to sustain periods of deliberate practice - Atkinson, Dawn (Journal of Writing Research, 2020)
Expertise research spanning a variety of domains has established the central role that deliberate practice plays in developing expertise. This type of practice demands time, internal motivation, effort, feedback, and determination to surpass existing levels of performance. To leverage the rigors of deliberate practice, the two expert textbook writers who participated in this study deployed the writing processes of reviewing, writing it down, and incubating while developing textbooks for English language teaching (ELT). Data collected mainly via concurrent verbalization—whereby the participants expressed their thoughts aloud while engaged in textbook writing—and pre- and post-concurrent verbalization interviews revealed that the participants called upon these processes in purposeful ways as metacognitive strategies used to maximize writing effectiveness, with metacognition operationalized here as the participants’ knowledge and recognition of how they thought and worked. This study provides insight into how textbooks are written in practice and thus has implications for the research field of materials development; the findings also point to practical strategies that might be utilized by those who write language learning materials.